Prevalence of Substance Use in Medical and Dental Students of a Medical University of Nepal - Sapkota, Nidesh; Pudasaini, Garima; Baral, Binav; Bhagat, Umesh; Agrawal, Diksha; Baral, Dharani Dhar (Journal of BP Koirala Institute of Health Sciences, 2020)
Introduction: Medical and Dental students are vulnerable to higher levels of psychological distress than other age matched peers. Many studies reveal that there is high prevalence of psychoactive substance use and psychiatric co-morbidities among them. Objective: To identify prevalence of substance use (alcohol, nicotine, cannabis) among medical and dental students. Methods: A cross sectional study was done among medical and dental students (2nd year to interns) of B PKIHS. A total of 600 students were enrolled through systematic random sampling and only 588(98%) responded. Semi-structured questionnaire was used which included socio-demographic variables, AUDIT (Alcohol Use Disorders Identification Test), Fagerstrom (for Nicotine dependence) and Cannabis Abuse Screening Test (CAST). Result: The mean age of participants was 22±2years. Among them, 61.2% (360) were male; 69.7% (410) were MBBS; 90.5% (532) were Nepalese and 9.5% (56) were Indians. The prevalence of alcohol users was 47.75% (281) in which 32% (90) were harmful users. Among 19.55% (115) nicotine users; 56.5% (65), 37.4% (43), 6.1% (7) had low, low to moderate and moderate dependence respectively. The prevalence of cannabis users was 9% (53) with 45.3% (24), 18.9% (10) having low and high addiction respectively. Conclusion: High percentage of medical and dental students showed substance use, harmful use and dependence. It is expected that they have knowledge about the harmful consequences of psychoactive substances.